2019
DOI: 10.1101/765727
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Transcriptomic response ofNitrosomonas europaeatransitioned from ammonia- to oxygen-limited steady-state growth

Abstract: word count: 250 34 Text word count: 4885 35 36 3 Abstract 37Ammonia-oxidizing microorganisms perform the first step of nitrification, the oxidation of 38 ammonia to nitrite. The bacterium Nitrosomonas europaea is the best characterized ammonia oxidizer to 39 date. Exposure to hypoxic conditions has a profound effect on the physiology of N. europaea, e.g. by 40 inducing nitrifier denitrification, resulting in increased nitric and nitrous oxide production. This metabolic 41 shift is of major significance in agri… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 87 publications
1
1
0
Order By: Relevance
“…Depending on the environmental conditions, the various amoC homologs in the genome might provide different activity profiles to the AMO complex. Previous transcriptional studies showed that additional monocistronic amoC subunits found in some terrestrial AOB aid in maintaining AMO enzyme stability during stressful conditions [78][79][80]. Together, our findings suggest a pivotal role of the amoC3 gene in the ammonia oxidation activity of N. viennensis EN76 grown on air-exposed solid surfaces.…”
Section: Oxidative Stress Responsessupporting
confidence: 65%
“…Depending on the environmental conditions, the various amoC homologs in the genome might provide different activity profiles to the AMO complex. Previous transcriptional studies showed that additional monocistronic amoC subunits found in some terrestrial AOB aid in maintaining AMO enzyme stability during stressful conditions [78][79][80]. Together, our findings suggest a pivotal role of the amoC3 gene in the ammonia oxidation activity of N. viennensis EN76 grown on air-exposed solid surfaces.…”
Section: Oxidative Stress Responsessupporting
confidence: 65%
“…2c and 3a). Similarly, the AMO transcriptions were observed increased in Nitrosomonas europaea pure cultures during oxygen-limited growth [73] and a nitrifying enrichment culture when its SOUR was constrained by heavy metals [9]. Overproduced AMO may contribute to the maintenance of ammonia oxidization under Cr pressure [74].…”
Section: Discussionmentioning
confidence: 94%